The Thousand and one nights and twentieth-century fiction : intertextual readings - Leeuwen, Richard van. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2018)
It is gradually being acknowledged that the Arabic story-collection Thousand and One Nights has had a major influence on European and world literature. This study analyses the influence of Thousand and One Nights , as an intertextual model, on 20th-century prose from all over the world. Works of approximately forty authors are examined: those who were crucial to the development of the main currents in 20th-century fiction, such as modernism, magical realism and post-modernism. The book contains six thematic sections divided into chapters discussing two or three authors/works, each from a narratological perspective and supplemented by references to the cultural and literary context. It is shown how Thousand and One Nights became deeply rooted in modern world literature especially in phases of renewal and experiment.